PEMAKNAAN GURU TERHADAP PEMENUHAN HAK ANAK MELALUI PENERAPAN SEKOLAH RAMAH ANAK DI SEKOLAH DASAR - Nurikhsani, Fadilla Aisah; Handoyo, Eko; Waluyo, Edi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The fulfillment of children’s rights in primary schools is a crucial aspect of creating a safe, fair, and participatory learning environment. This study aims to explore teachers’ meaning-making of children’s rights fulfillment within the context of the implementation of Child-Friendly Schools (CFS). The study employed a qualitative approach with a case study design conducted at SD Muhammadiyah Purwokerto. The research participants consisted of six teachers selected through purposive sampling. Data were collected through in-depth interviews and classroom observations and analyzed using Miles, Huberman’s, and Saldaña interactive data analysis model. The findings indicate that teachers primarily interpret the fulfillment of children’s rights as efforts to create a sense of safety, ensure fair treatment, and provide opportunities for students’ participation in learning activities. These interpretations are reflected in classroom pedagogical practices, particularly in teacher–student relationships and the creation of a learning climate that supports student engagement. However, the fulfillment of children’s rights in classroom practice faces several challenges, including academic pressure, curriculum demands, and the diversity of students’ characteristics. In addition, although relevant training has been provided, such training is not yet sufficiently contextual and practice-oriented, leading teachers to rely heavily on personal teaching experience in implementing children’s rights principles.